A Longitudinal Investigation of Empathic Exchanges in Online Cancer Support Groups: Message Reception and Expression Effects on Patients' Psychosocial Health Outcomes. Issue 6 (3rd June 2019) - Han, Jeong Yeob; Kim, Eunkyung; Lee, Yen-I; Shah, Dhavan V.; Gustafson, David H.
Abstract : Recent studies have devoted attention to the effects of both expression and reception in communication process. However, there remain both theoretical and methodological complexities concerning whether and under what condition message expression and reception play significant but different roles in explaining various psychosocial health outcomes. Relying on theoretical insights from the social support literature and methodological innovations offered by computational social science, this study aims to examine the effects of empathic exchanges on cancer patient's short- and long-term psychosocial health outcomes. Our findings suggest that both empathy expression and reception are crucial to attaining benefits for cancer patients, each predicting differential cognitive and affective health outcomes. Further, our finding supports the stress-buffering hypothesis such that empathy reception provides a beneficial effect for patients who experienced a higher degree of depression associated with their cancer diagnosis and follow-up treatments.